2020
DOI: 10.1056/nejmoa1913805
|View full text |Cite
|
Sign up to set email alerts
|

Inclisiran for the Treatment of Heterozygous Familial Hypercholesterolemia

Abstract: BACKGROUND Familial hypercholesterolemia is characterized by an elevated level of low-density lipoprotein (LDL) cholesterol and an increased risk of premature atherosclerotic cardiovascular disease. Monoclonal antibodies directed against proprotein convertase subtilisin-kexin type 9 (PCSK9) have been shown to reduce LDL cholesterol levels by more than 50% but require administration every 2 to 4 weeks. In a phase 2 trial, a twice-yearly injection of inclisiran, a small interfering RNA, was shown to inhibit hepa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
445
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 542 publications
(474 citation statements)
references
References 23 publications
14
445
0
15
Order By: Relevance
“…The metabolic changes induced by another way of pharmacologic inhibition of PCSK9, i.e., with the small interfering RNA inclisiran, are similar to those observed under treatment with antibodies against PCSK9 (Raal et al, 2020).…”
Section: Consequences Of Therapeutic Inhibition Of Pcsk9mentioning
confidence: 63%
“…The metabolic changes induced by another way of pharmacologic inhibition of PCSK9, i.e., with the small interfering RNA inclisiran, are similar to those observed under treatment with antibodies against PCSK9 (Raal et al, 2020).…”
Section: Consequences Of Therapeutic Inhibition Of Pcsk9mentioning
confidence: 63%
“…Compared with the placebo group, the Inclisiran group had no serious adverse reactions. In the subsequent phase III clinical study of Inclisiran, compared with placebo, LDL-C in Inclisiran group was significantly reduced, with the efficacy able to last for more than 18 months ( Raal et al, 2020 ; Ray et al, 2020 ). The introduction of PCSK9 inhibitors is a milestone in the treatment of FH, and Inclisiran provides a new lipid-lowering technology.…”
Section: From Diagnosis Methods To Therapy Strategies Of Fh Based On mentioning
confidence: 98%
“…Recently, the results of the phase 3 ORION-9 trial demonstrated the safety and efficacy of inclisiran in patients with heterozygous FH [41] (Table 1).…”
Section: Administering Inclisiran Every 6 Months Lowers Ldl-c By Apprmentioning
confidence: 99%